LINKING WORK LIFE BALANCE AND ORGANIZATIONAL SUPPORT TO EMPLOYEE PERFORMANCE THROUGH SAFETY CULTURE: EVIDENCE FROM A MARITIME REGULATORY AGENCY - Sopiansyah; Siti Maria; Anisa Kusumawardani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines how work-life balance and organizational support influence employee performance through safety culture at the Samarinda Class I Harbormaster and Port Authority Office. This study departs from the theoretical debate on how individual resources and institutional support translate into performance in high-risk organizations. Using a quantitative explanatory approach with partial least squares structural equation modeling analysis on 97 employees, this study found that work-life balance and organizational support significantly influenced safety culture and employee performance. Safety culture partially mediated this relationship, functioning as a collective mechanism that converts role balance and institutional support into operational performance. The main contribution of this study is the affirmation of safety culture as an organizational capability that integrates individual well-being and organizational support to improve performance in the context of port regulation.